Analysis of quality of life in women after the diagnosis of breast cancer in a referral hospital for cancer in Northeast Brazil (Research, Society and Development, 2020)
Introduction: Breast cancer is one of the most prevalent among women and can provide traumatic experiences for women. Changes related to the appearance of this pathology can cause changes in mood, self-esteem and sexuality. This study aims to analyze the quality of life of women after the diagnosis of breast cancer. Methodology: This is a quantitative study with a cross-sectional design. The study population consisted of women who, on the date of collection of this study, had been diagnosed with breast cancer for at least 4 months and who remained under treatment at the cancer center. For data collection, a Previous Registration of women was made through the Registration Form, and then the application of the WHOQOL-Bref scale in order to assess the quality of life of women who were undergoing Breast Cancer treatment. Results: Most women interviewed (80%) rated their quality of life positively. While 48.3% expressed negative feelings, 91.7% were satisfied with the support received from friends. The quality of life related to the environment was the only one that did not present, in its majority, a good or very good classification. Conclusion: From the completion of this work, it is concluded that although the diagnosis of breast cancer can have negative impacts on the lives of women, most of them classify their quality of life as good or very good, suggesting that the therapeutic approach and the family support can mitigate the impacts of this diagnosis.